Prevalence of chronic hepatitis B virus infection in Thailand: a systematic review and meta-analysis - Leroi C. (2017)
© 2016 The Author(s) Objective To estimate the number of people living in Thailand with chronic hepatitis B (CHB), a major cause of liver cirrhosis and cancer, in view of the implementation of programs to prevent CHB complications. Methods Using PubMed/Medline and ScienceDirect, all studies reporting hepatitis B surface antigen (HBsAg) seroprevalence estimates conducted in Thailand and published between 1975 and 2015 were reviewed systematically. Pooled prevalence estimates and their 95% confidence intervals (CIs) were calculated, and potential sources of heterogeneity investigated. Results A high heterogeneity was observed between prevalence estimates. There was a significant decrease in the 150 estimates of HBsAg prevalence with more recent decades of birth (p  <  0.001), even before the implementation of the national universal immunization program in 1992. When restricted to the general population, the pooled prevalence estimate was 5.1% (95% CI 4.3–6.0%), which would translate to an estimated number of individuals with CHB living in Thailand in 2015 as high as three million. Conclusions The high burden of CHB in Asian countries is a major challenge for the incorporation of national programs to prevent CHB complications within health care systems.